Percutaneous patent ductus arteriosus closure in extremely low birth weight baby using Amplatzer Piccolo Occluder device - Kapoor, Saurabh; Kaur, Ramanjot; Baidwan, Amitoj Singh (International Journal of Contemporary Pediatrics, 2023)
Hemodynamically significant patent ductus arteriosus (PDA) is one of major morbidities seen in preterm babies. It can be closed using conservative, surgical and percutaneous device occlusion techniques. Transcatheter Amplatzer Piccolo Occluder is 1st FDA approved device available in India for closure of PDA in very preterm babies with weight >700 gm. In India, insufficient data is available pertaining to this procedure in extremely low birth weight babies.